2014
DOI: 10.1080/13632752.2014.945741
|View full text |Cite
|
Sign up to set email alerts
|

School exclusion in children with psychiatric disorder or impairing psychopathology: a systematic review

Abstract: Childhood psychiatric disorders are associated with a wide range of adverse outcomes including poor academic attainment. For some children these difficulties are recognised through school Special Educational Need procedures (SEN) but many others may remain unidentified and/or unsupported. In Britain, government data suggests disproportionate representation of children with a SEN among children permanently excluded from school.This review asks whether school-aged children with impairing psychopathology were mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 39 publications
1
35
0
1
Order By: Relevance
“…If other causes are ruled out and the problems persist with moderate impairment, referral to specialist services for a diagnosis is recommended. Younger children, more commonly boys, can present with difficulties at school and, in extremis, school exclusion, 6 whereas girls have more attentional difficulties and ADHD can often remain undiagnosed until later when academic demands become greater. A referral to secondary care will be greatly aided by additional multidisciplinary reports-for example, from professionals working within the education sector, such as teachers, educational psychologists, and pastoral support staff.…”
Section: How Is It Assessed and Diagnosed?mentioning
confidence: 99%
See 1 more Smart Citation
“…If other causes are ruled out and the problems persist with moderate impairment, referral to specialist services for a diagnosis is recommended. Younger children, more commonly boys, can present with difficulties at school and, in extremis, school exclusion, 6 whereas girls have more attentional difficulties and ADHD can often remain undiagnosed until later when academic demands become greater. A referral to secondary care will be greatly aided by additional multidisciplinary reports-for example, from professionals working within the education sector, such as teachers, educational psychologists, and pastoral support staff.…”
Section: How Is It Assessed and Diagnosed?mentioning
confidence: 99%
“…4 In combination, these factors can create secondary adversities, such as greater risk of poor school attainment and exclusion, misuse of substances, and involvement with the criminal justice system ( fig 1⇓). [5][6][7][8] ADHD is a disorder that attracts considerable debate and controversy. Data indicate that in some areas overdiagnosis is a problem, 9 with concerns about the misuse of psychostimulants raised within the healthcare profession and elsewhere.…”
mentioning
confidence: 99%
“…Incidence and typical age of onset varies by diagnosis, but all can have negative impacts on numerous facets of life including daily functioning, social interactions, and educational achievement (e.g. McLeod and Kaiser, 2004, Parker et al, 2015, Van Ameringen et al, 2003). Research has demonstrated that the majority of adult psychopathologies begin in childhood and adolescence (Kim-Cohen et al, 2003), with the poorest prognosis for those whose problems begin early and persist (Copeland et al, 2015, Kessler et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Attention‐deficit hyperactivity disorder (ADHD) is a developmental disorder characterized by developmentally inappropriate and pervasive levels of hyperactivity, inattention and impulsivity (APA ). The core symptoms of ADHD may affect a child's functioning in an educational environment, and a diagnosis of ADHD is associated with poor school outcomes including poorer reading ability (Rabiner et al ), writing and mathematics (Rodriguez et al ), lower school grades (Loe & Feldman ) and exclusion from school (Parker et al ). Childhood hyperactivity has been shown to predict adolescent behavioural and academic problems and may reduce the number of qualifications obtained (McGee et al ).…”
mentioning
confidence: 99%